Pembatalan Sepihak Oleh Penjual Dalam Perjanjian Jual Beli Online - Lasut, Tesalonica Heavenly; Akyuwen, Rory Jeff; Kuahaty, Sarah Selfina (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: At first, the community carried out conventional buying and selling transactions where the sellers and buyers met face to face. However, with the very rapid development of technology, modern society is more inclined to carry out buying and selling transactions online without face-to-face meetings. This has a positive but also negative impact due to the fact that what is happening with the development of online buying and selling transactions triggers the emergence of unscrupulous people who take advantage of this situation. Among them are related to the seller who sometimes terminates the agreement by unilaterally canceling the buyer who has made a payment transaction for an item or product being traded.Purposes of the Research:  The purpose of this study is to find out and examine whether the unilateral cancellation by the seller is an act of default and what are the legal remedies against the buyer who is harmed by the seller's unilateral cancellationMethods of the Research: This research is a normative juridical. The approach used in this research is the statute approach and the conceptual approach. The sources of legal materials are primary, secondary and tertiary where the collection of legal materials is carried out using library research. Furthermore, it is analyzed qualitatively by processing, analyzing and constructing the results as a whole so that in the end it can answer the problems studied.Results of the Research: The results of this study indicate that the cancellation of online buying and selling agreements unilaterally by the seller against the buyer is an act of default because the seller does not have the effort to fulfill the achievements or obligations that should be carried out in accordance with the rules in force in Article 7 of Law Number 8 of 1999 concerning Consumer Protection where the seller do not fulfill their achievements at all and are declared negligent in fulfilling their achievements. The process of resolving consumer disputes can be resolved through two channels, namely through litigation with lawsuits to court and non-litigation through the Consumer Dispute Settlement Agency (known as BPSK) through conciliation, mediation or arbitration and the Non-Governmental Consumer Protection Agency (known as LPKSM).